Turing Computability: Theory and Applications - Soare, Robert I (Theory and Applications of Computability, 2016)
This book emphasizes three very important concepts: computability, as opposed to recursion or induction; classical computability; and the art of computability, a skill to be practiced but also important in an esthetic sense of beauty and taste in mathematics.